A systematic study of dyeing polybutylene succinate fibres. (21st November 2019) - Li, Dawei; Zhang, Bingjie; Wang, Shugen; Zhou, Chang E.; Sun, Chang; Zha, Quanliang
Abstract: Biodegradable polybutylene succinate (PBS) fibre is a new type of textile fibre, but its application in the textile industry is limited by the lack of related dyeing methods. In this study, the solubility parameters of PBS fibres are calculated, and solvent dyes with similar solubility parameters are proposed to dye PBS fibres to show that the dyeing scheme creatively resolves the difficulty in dyeing PBS fibres. The technical parameters of suitable dyes, and the dyeing conditions with ethanol as the dyeing medium, consisted of a dyeing temperature of 90°C, a dyeing time of 30 minutes and a liquor ratio of 30:1. The dyeing results show that the levelling property is good, the dyebath exhaustion is high, and the washing fastness, the rubbing fastness and the perspiration fastness index of the dyed fibres are satisfactory.